The Spread of Christianity in the First Four Centuries : Essays in Explanation - Harris, William V. (Brill Book Archive Part 1, ISBN: 9789004472495., 2005)
The Spread of Christianity in the First Four Centuries: Essays in Explanation attempts to show how contemporary historical scholarship, or rather a selection of its exponents, views the perennial question why a new religion, indeed a new kind of religion, succeeded in subverting the other religions of the Roman Empire in the first three centuries and in the generations immediately following the 'conversion' of the usurper Constantine in 312.